An anthracene-9-carboxylic acid-based [Cu20] cluster templated by a bromine anion for heterogeneous catalytic chemical fixation of carbon dioxide. Issue 45 (27th October 2022) - Dong, Dapeng; Tian, Xueqin; Wu, Pengyan; Wang, Jian; Huang, Jindou; Zhao, Haiyan; Liu, Dedi; Zhang, Zhenyi
Abstract : A highly stable copper-oxo cluster was constructed from the conjugated macromolecule anthracene-9-carboxylic acid templated by bromine anion as highly efficient heterogeneous catalyst for chemical fixation of carbon dioxide. Abstract : Copper-oxo clusters have been of great interest due to their fascinating structures and potential applications. However, it was difficult to construct copper clusters using conjugated macromolecules by a conventional solvent method due to their insolubility. Herein, a hydroxo-bridged [Cu20 ] cluster was self-assembled through the employment of solvothermal techniques by using the conjugated macromolecule anthracene-9-carboxylic acid and copper bromide or cuprous bromide. The bromine anion as a template has been found to play a crucial role in the synthesis of the [Cu20 ] cluster compared to other anion-based copper salts, which form the paddlewheel [Cu2 ] cluster. The catalytic tests showed that the [Cu20 ] cluster exhibited an excellent conversion efficiency in the cycloaddition reaction of CO2 with epichlorohydrin. The turnover number (TON) was about 58 823, while the turnover frequency (TOF) was approximately 19 607 h −1 . As far as we know, these values in this work for metal–organic catalysts were the highest among the previously reported catalytic data on the cycloaddition of CO2 to epoxide under similar conditions. The cycling test showed that the catalytic activity of the [Cu20 ] cluster in the cycloaddition of CO2 to epoxide was retained for five repeated cycles, indicating that the catalytic reaction was actually heterogeneous. The high catalytic efficiency and stability enable the use of raw power station flue gas, which reveals the broad prospect of this copper-oxo cluster in the industrial application of CO2 fixation.